Al Quran and Hadits as Ideas and Sources of Stories in Ahmad Tohari’s Novels - Abdul Wachid Bambang Suharto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2022)
The focus of this study is to reveal the religious dimension as a story and the Qur’an and Hadith as ideas and sources of stories in Ahmad Tohari’s works. The method used in this study is a descriptive interpretive method. Data were collected through literature study, interviews, and observations. Data analysis was carried out using qualitative content analysis techniques. The result is that Ahmad Tohari’s works are a sublimation of religious values ​​derived from the Qur’an and Hadith. Ahmad Tohari uses the two sources of Islamic law as a source of stories. Thus, although Ahmad Tohari’s works are known as literary works of human value, they contain religious values ​​or religiosity. Many short stories and novels have raised issues about the economic and social life of the community or the marginalized. However, the work is a literary work that has conditions with religious and prophetic values ​​originating from the Qur’an and Hadith and makes religion a story.